2021
DOI: 10.3390/en14041111
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Emission Inventory in an Urban Zone of West Africa: Case of Yopougon City (Abidjan, Côte d’Ivoire)

Abstract: Road traffic emission inventories based on bottom-up methodology, are calculated for each road segment from fuel consumption and traffic volume data obtained during field measurements in Yopougon. High emissions of black carbon (BC) from vehicles are observed at major road intersections, in areas surrounding industrial zones and on highways. Highest emission values from road traffic are observed for carbon monoxide (CO) (14.8 t/d) and nitrogen oxides (NOx) (7.9 t/d), usually considered as the major traffic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…At the MACA site (Fig. 4d), the work of Doumbia et al 34,41 showed that the flow of vehicles on the secondary roads reached its maximum (7000 vehicles per hour) between 7:00–9:00 UTC. This closely corresponds to the PM 2.5 peak observed at 7:00 UTC at this site.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…At the MACA site (Fig. 4d), the work of Doumbia et al 34,41 showed that the flow of vehicles on the secondary roads reached its maximum (7000 vehicles per hour) between 7:00–9:00 UTC. This closely corresponds to the PM 2.5 peak observed at 7:00 UTC at this site.…”
Section: Resultsmentioning
confidence: 96%
“…The vehicles are a major source of air pollution in this area due to the age and the lack of maintenance of these vehicles. 33,34 This site is located at the western edge of the forest of the Banco National Park, which has an area of 3474 ha. 35 This forest with large centennial trees is considered as the main hydraulic reservoir and the green lung of the city of Abidjan.…”
Section: Introductionmentioning
confidence: 99%
“…The pollution emission inventories are now a widely used tool in environmental protection [1][2][3][4], which has been supported by sanctioned procedures enabling the critical assessment of the impact of civilization-related activities on the environment. Pollutant emissions from road transport play a special role in environmental protection, largely due to the extensive use of road vehicles, especially in the regions with high population densities, i.e., large urban agglomerations.…”
Section: Introductionmentioning
confidence: 99%